Circulating MicroRNAs as Emerging Diagnostic Tools in Cervical Intraepithelial Neoplasia. - Amna Liaqat, Sehrish Sabir, Ayesha Sajjad, Beenish Zafar, Tahmeena Sarfraz, Nadia Mahmood, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Cervical intraepithelial neoplasia (CIN) represents a spectrum of premalignant lesions with thepotential to progress to invasive cervical carcinoma if left untreated. Conventional diagnosticapproaches, such as Pap smears and colposcopy, have limitations in sensitivity and reproducibility. Circulating microRNAs